1993
DOI: 10.1111/j.1464-410x.1993.tb15906.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Desmodium styracifolium‐triterpenoidon Calcium Oxalate Renal Stones

Abstract: We have studied the inhibitory effects of Desmodium styracifolium-triterpenoid (Ds-t) (extracted from Desmodium styracifolium (Osbeck) Merr, a herbal medicine) on the formation of calcium oxalate renal stones induced experimentally by ethylene glycol (EG) and 1 alpha(OH)D3 (1 alpha D3) in rats. The incidence of urinary stone formation was 81% in the control group, which received EG and 1 alpha D3, and 29% in the Ds-t group, which received EG and 1 alpha D3 supplemented by Ds-t. The serum calcium (Ca) concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 13 publications
1
8
0
1
Order By: Relevance
“…The reduced serum calcium level correlates with an increased urinary calcium excretion and a subsequent deposition of calcium oxalate in the kidney as a consequence of treatment with EG. Similar results were obtained from other studies (Al-Attar, 2010;Rajagopal, 1977;Hiramaya et al, 1993). In contrast, a study by Touhami et al (2007) showed an elevated serum calcium in the EG/AC treated group; the cause of which was not explained (Touhami, 2007).…”
Section: Discussionsupporting
confidence: 87%
“…The reduced serum calcium level correlates with an increased urinary calcium excretion and a subsequent deposition of calcium oxalate in the kidney as a consequence of treatment with EG. Similar results were obtained from other studies (Al-Attar, 2010;Rajagopal, 1977;Hiramaya et al, 1993). In contrast, a study by Touhami et al (2007) showed an elevated serum calcium in the EG/AC treated group; the cause of which was not explained (Touhami, 2007).…”
Section: Discussionsupporting
confidence: 87%
“…Two alkaloid compounds namely, aminoglucosyl glycerolipid (118) and glycosphingolipid (106), isolated from Desmodium gangeticum exhibited antileishmanial activities in vitro, which could be responsible for the antileishmanial of its host plant (Iwu et al, 1992;Jabbar et al, 2004;Singh et al, 2005;Mishra et al, 2005). Soyasaponin I (132), a terpenoid compound isolated from Desmodium styracifolium, was shown to be effective against urolithiasis which is corresponding with its host plant (Kubo et al, 1989b;Hirayama et al, 1993).…”
Section: Resultsmentioning
confidence: 98%
“…In addition, there was a greater increase in urine volume in the Soyasaponin I treated group than that in the control group. All the findings suggest that the inhibition on the formation of Ca oxalate stones in rat kidneys by Soyasaponin I may be resulting from increasing the output of urine, decreasing the excretion of Ca and increasing the urinary excretion of citrate (Kubo et al, 1989b;Hirayama et al, 1993).…”
Section: Antinephrolithic Activitymentioning
confidence: 95%
“…A 52% in stone burden was observed in Ds-t fed rats compared to control group animals. This data suggests that Ds-t reduces stone formation of pure Ca oxalate crystals in the rat kidney (23).…”
Section: Jin Qian Cao (Desmodium Styracifolium Merr)mentioning
confidence: 62%